Gelatine source labelling in gelatine-containing products: a product analysis - Tukiran, Nur Azira; Basri Halimuddin, Izzah Al-Husna (IIUM Press, 2026)
Gelatine is a widely used ingredient in food and health supplement products, valued for its functional properties but controversial due to its animal source. For Muslim consumers, the halal status of gelatine depends on the source animal and slaughtering process, while for others, allergenicity and dietary restrictions (e.g., vegetarianism) require clear source disclosure. In Malaysia, the Food Regulations 1985 [Part VIII: Standards and particular labelling requirements for food 153(4)] mandate transparency in gelatine labelling, including the requirement to state the source animal. This study evaluated the extent of disclosure of gelatine sources among gelatine-containing products marketed in Malaysia. A total of 120 products across confectionery, health supplements, and bakery ingredient categories were assessed using a structured checklist. Findings showed that 78% of products declared the source of gelatine, whereas 22% listed only the generic term "gelatine" without specifying the source. Halal logos were displayed on 73% of the products, with variation observed across product categories. The presence of products without clear gelatine source information indicates gaps between regulatory expectations and marketplace practice, which may affect religious assurance, allergen risk awareness, and consumer confidence. Strengthening consistency in source declaration, supported by responsible industry practice and accessible verification mechanisms, may enhance transparency and support informed decision-making among consumers in Malaysia.